Heat-conducting silica gel and preparation method thereof

By introducing thermoplastic elastomers and frozen-pressed chopped carbon fibers into the thermally conductive silicone, a three-dimensional crosslinking network structure is formed, which solves the problem of thermally conductive silicone becoming soft at high temperatures and improves its temperature tolerance and thermal conductivity.

CN119320562AInactive Publication Date: 2025-01-17DONGGUAN ZHENGNIAN SILICONE FLUORINE MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411609554.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Thermal conductive silicone tends to soften at high temperatures, resulting in insufficient temperature tolerance and affecting its performance.

Method used

A preparation method is adopted to improve thermal conductivity and temperature tolerance by introducing thermoplastic elastomers and frozen-pressed chopped carbon fibers into the silicone system. The specific steps include stirring and mixing carbon fiber with polyvinyl alcohol solution, uniformly mixing with components such as silica gel after freezing and pressing, forming a three-dimensional crosslinking network structure through crosslinking and curing and cooling processes, and improving the toughness and thermal conductivity of the material.

Benefits of technology

By introducing thermoplastic elastomers and frozen-pressed chopped carbon fibers, the temperature resistance and thermal conductivity of silicone are improved, ensuring that the product can maintain good performance at high temperatures, and can quickly respond to thermal stress during subsequent temperature shocks and Release stress.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005130592240000071
    Figure BDA0005130592240000071
Patent Text Reader

Abstract

The invention belongs to the technical field of heat conduction materials. The invention relates to silica gel, in particular to heat-conducting silica gel and a preparation method thereof. The preparation method comprises the following specific preparation steps: taking 50-60 parts by weight of vinyl silicone oil, 0.6-0.7 part by weight of a platinum catalyst, 8-10 parts by weight of hydrogen-containing silicone oil, 6-8 parts by weight of a heat-conducting filler and 8-10 parts by weight of a thermoplastic elastomer; wherein the heat-conducting filler is frozen and squeezed chopped carbon fibers; the preparation method of the frozen and squeezed short carbon fiber comprises the following steps: stirring and mixing carbon fiber and a polyvinyl alcohol solution, freezing into a solid state at the temperature of-30 to-45 DEG C, and then freezing and squeezing for 20-30 seconds at the pressure of 10-15 MPa to obtain a squeezed material; performing vacuum freeze drying on the squeezed material to obtain frozen and squeezed chopped carbon fibers; the preparation method comprises the following steps: heating, stirring and uniformly mixing the vinyl silicone oil, the platinum catalyst, the heat-conducting filler and the thermoplastic elastomer, adding the hydrogen-containing silicone oil, continuously stirring and uniformly mixing, injecting into a mold, preserving heat and curing, cooling and demolding to obtain the heat-conducting silica gel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of thermal conductive materials, and more specifically, relates to a thermal conductive silica gel and a preparation method thereof. Background Art

[0002] Thermally conductive silicone is a kind of silicone that is mainly made of organic silicone and mixed with fillers, thermal conductive materials and other polymer materials. It has good thermal conductivity and electrical insulation properties. It is mainly used to conduct heat and improve the heat dissipation effect. It is widely used between electronic components and radiators, and filled in the heat dissipation parts of electronic equipment to increase the heat dissipation area, improve the heat dissipation efficiency, and prevent components from overheating and damage.

[0003] At present, thermal conductive silicone may have insufficient temperature tolerance during actual use. Specifically, thermal conductive silicone may become soft at high temperatures, affecting its performance, such as direct bonding with the substrate.

[0004] The reasons for the above problems may be mainly due to the following aspects: Thermal stability of the silicone matrix: The silicone matrix of thermal conductive silicone directly affects its temperature resistance. Ordinary organic silicone contains organic groups and is prone to degradation reactions at high temperatures, so its temperature resistance is relatively poor; Type and amount of filler: The thermal conductivity of thermal conductive silicone mainly comes from fillers. Inorganic fillers such as alumina and boron nitride have good high-temperature stability. However, excessive filler dosage may affect the flexibility of silicone and cause cracking at high temperatures; Cross-linking density: The cross-linking density of thermal conductive silicone directly affects its temperature resistance. The higher the cross-linking density, the greater the chemical bond force between molecules, and the less destructive effect of thermal motion on the material, thereby improving the heat resistance. However, excessive cross-linking may also make the material fragile; In addition to the above factors, the temperature resistance of thermal conductive silicone may also be affected by factors such as environmental humidity and radiation.

[0005] Therefore, how to develop a thermally conductive silicone with better temperature tolerance is one of the technical difficulties that technicians in this field still need to overcome. Summary of the invention

[0006] The technical problem to be solved by the present invention is that the shape of the existing thermally conductive silica gel is easily changed during the use of the product, thereby causing the problem of insufficient temperature tolerance of the product. Based on the above problem, the present invention provides a thermally conductive silica gel and a preparation method thereof.

[0007] The purpose of the invention is to provide a thermally conductive silica gel.

[0008] Another object of the present invention is to provide a method for preparing thermally conductive silica gel.

[0009] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0010] A method for preparing thermally conductive silica gel, the specific preparation steps comprising:

[0011] Weighing raw materials:

[0012] By weight, take 50-60 parts of vinyl silicone oil, 0.6-0.7 parts of platinum catalyst, 8-10 parts of hydrogenated silicone oil, 6-8 parts of thermal conductive filler, and 8-10 parts of thermoplastic elastomer;

[0013] Wherein, the thermally conductive filler is freeze-pressed chopped carbon fiber;

[0014] The preparation of the freeze-pressed chopped carbon fibers comprises:

[0015] The carbon fiber and polyvinyl alcohol solution are stirred and mixed in a mass ratio of 1:10-12, and then frozen into a solid state at a temperature of -30-45°C, and then frozen and pressed for 20-30s at a pressure of 10-15MPa to obtain a pressed material;

[0016] The pressed material is vacuum freeze-dried to obtain freeze-pressed chopped carbon fibers;

[0017] Preparation of thermal conductive silicone:

[0018] After heating and stirring the vinyl silicone oil, platinum catalyst, thermal conductive filler and thermoplastic elastomer to mix evenly, add hydrogen-containing silicone oil, continue to stir and mix evenly, inject into the mold, heat-insulate and cure, cool, and demold to obtain thermal conductive silicone.

[0019] The technical effects of the above technical solution are:

[0020] By introducing a certain amount of thermoplastic elastomer and an appropriate amount of freeze-pressed chopped carbon fiber into the silicone system, the thermal conductivity of the silicone can be improved while enhancing the product's tolerance to temperature.

[0021] Specifically, the introduction of thermoplastic elastomer, during the product processing, after being heated, the polymer chain stretches, and it is easy to penetrate into the three-dimensional cross-linked network structure formed by silica gel when the system is cross-linked and cured, and in the process of penetration and diffusion, it can drive the diffusion and penetration of the frozen pressed short carbon fiber, thereby realizing the uniform toughening process of the three-dimensional cross-linked network structure, and relying on the frozen pressed short carbon fiber to provide a heat conduction path while providing effective support, because, with the cross-linking and curing, and the curing of the thermoplastic elastomer in the subsequent cooling process, the internal stress formed in the cooling and curing process can be dispersed to the three-dimensional cross-linked network structure by relying on the carbon fiber, and, when it is subsequently subjected to temperature shock, the thermal stress generated by the temperature can be quickly transmitted to the inside through the short carbon fiber, and the presence of the thermoplastic elastomer can release the stress through a certain degree of elastic deformation, but the inventor found that the addition of less thermoplastic elastomer, even after being heated and melted, can construct a system with a certain viscosity with carbon fiber. On the contrary, if the amount added is too much, it is easy to melt and flow after being heated, which is not conducive to the temperature sensitivity of the product.

[0022] The reason why the added carbon fiber is freeze-pressed chopped carbon fiber is, first of all, that the chopped carbon fiber is desired because the carbon fiber is too long and is easy to curl or entangle with each other. It is difficult to form a homogeneous system in the system and between the molecular chains stretched during the processing of the thermoplastic elastomer and the cross-linked network structure formed by the cross-linking and curing of the silicone. Cutting it during the processing can be beneficial to its uniform dispersion. In particular, the inventors found that after cutting, it can be arranged at different angles in the system, so that the thermal conductivity of the product at all angles is relatively uniform, so that local failure is not easy to occur when heated; secondly, the reason why freeze pressing is used to cut the carbon fiber is that in this process, after the polyvinyl alcohol solution is frozen and solidified, ice crystals can be formed between the fibers. As the pressing pressure is generated, the ice crystals break and the fibers are broken, and the broken fibers are not easy to agglomerate. Therefore, adding it to the system can obtain a better dispersion effect.

[0023] Furthermore, the aspect ratio of the carbon fiber is 200-400, and the average length of the carbon fiber is 0.3-0.5 mm.

[0024] Furthermore, the thermoplastic elastomer is selected from any one of styrene-butadiene-styrene triblock copolymers or isoprene-substituted butadiene block styrene polymers.

[0025] Selecting a suitable thermoplastic elastomer can effectively change state and melt at the corresponding processing temperature, thereby helping the system to be quickly uniform.

[0026] Furthermore, the preparation of the thermally conductive silica gel further comprises:

[0027] Vinyl silicone oil, platinum catalyst, thermal conductive filler and thermoplastic elastomer are heated, stirred and mixed for 2-4 hours at a temperature of 80-100°C and a stirring speed of 400-500r / min, and then hydrogen-containing silicone oil is added. After continuing to stir and mix for 30-60 minutes, it is injected into a mold, and after heat preservation and curing at a temperature of 80-100°C, it is cooled and demolded to obtain thermal conductive silicone.

[0028] Furthermore, the preparation of the freeze-pressed chopped carbon fibers also includes:

[0029] The carbon fiber and the polyvinyl alcohol solution with a mass fraction of 6-8% are stirred and mixed in a mass ratio of 1:10-12, and then frozen into a solid state at a temperature of -30-45°C, and then frozen and pressed for 20-30s at a pressure of 10-15MPa to obtain a pressed material;

[0030] After the pressed material is completely thawed at room temperature, 8-10% of the mass of the pressed material is added with a silane coupling agent, the pH is adjusted to 7.6-7.8, and the reaction is stirred for 30-40 minutes at a stirring speed of 300-380 r / min, and then vacuum freeze-dried to obtain freeze-pressed chopped carbon fibers.

[0031] By further introducing a silane coupling agent, the interfacial compatibility between the chopped carbon fiber and the silica gel can be further improved, thereby improving the overall uniformity of the system.

[0032] Furthermore, the silane coupling agent is selected from any one of silane coupling agent KH-540, silane coupling agent KH-550, silane coupling agent KH-560, silane coupling agent KH-570, and silane coupling agent KH-580.

[0033] Furthermore, the preparation of the freeze-pressed chopped carbon fibers also includes, when adding the silane coupling agent, adding dopamine in an amount of 3-5% by mass of the silane coupling agent.

[0034] In a weakly alkaline environment, dopamine can undergo a certain amount of oxidative self-polymerization, thereby forming a coating layer on the surface of the carbon fiber. This coating layer can form adhesion with the organic thermoplastic elastomer and the cross-linked network of silicone, thereby ensuring that the heat conduction at the interface of the product will be faster during the heating process.

[0035] A thermally conductive silica gel is prepared by the above-mentioned preparation method. DETAILED DESCRIPTION

[0036] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0037] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0038] Example 1

[0039] Preparation of freeze-pressed chopped carbon fibers:

[0040] The carbon fiber and the polyvinyl alcohol solution with a mass fraction of 8% were mixed in a mass ratio of 1:10, stirred and mixed with a stirrer at a speed of 300 r / min for 40 minutes, and then frozen into a solid state at a temperature of -30°C, and then freeze-pressed for 20 seconds at a pressure of 10 MPa to obtain a pressed material;

[0041] The aspect ratio of the carbon fiber is 200, and the average length of the carbon fiber is 0.3 mm;

[0042] After the pressed material is completely thawed at room temperature, it is introduced into a reactor, and a silane coupling agent of 8% by weight of the pressed material and dopamine of 3% by weight of the silane coupling agent are added, and the pH of the material in the reactor is adjusted to 7.6. Under the condition of a stirring speed of 300 r / min, the stirring reaction is carried out for 30 minutes, and then the material is discharged, and then vacuum freeze-dried to obtain freeze-pressed chopped carbon fibers; and the carbon fibers are used as thermal conductive fillers;

[0043] The silane coupling agent is selected from silane coupling agent KH-540;

[0044] Weighing raw materials:

[0045] By weight, take 50 parts of vinyl silicone oil, 0.6 parts of platinum catalyst, 8 parts of hydrogenated silicone oil, 6 parts of thermal conductive filler, and 8 parts of thermoplastic elastomer;

[0046] Preparation of thermal conductive silicone:

[0047] Vinyl silicone oil, platinum catalyst, thermal conductive filler and thermoplastic elastomer are heated, stirred and mixed for 4 hours at a temperature of 80°C and a stirring speed of 400r / min, so that the thermoplastic elastomer is fully melted and the components are evenly mixed; hydrogen-containing silicone oil is then added, and the mixture is stirred and mixed for 30 minutes, and then injected into a mold, and after being cured at a temperature of 80°C, cooled, and demolded, the thermal conductive silicone is obtained;

[0048] The thermoplastic elastomer is selected from styrene-butadiene-styrene triblock copolymers.

[0049] Example 2

[0050] Preparation of freeze-pressed chopped carbon fibers:

[0051] The carbon fiber and the polyvinyl alcohol solution with a mass fraction of 7% were mixed in a mass ratio of 1:11, stirred and mixed with a stirrer at a speed of 300 r / min for 40 minutes, and then frozen into a solid state at a temperature of -35°C, and then freeze-pressed for 25 seconds at a pressure of 12 MPa to obtain a pressed material;

[0052] The aspect ratio of the carbon fiber is 300, and the average length of the carbon fiber is 0.4 mm;

[0053] After the pressed material is completely thawed at room temperature, it is introduced into a reactor, and a silane coupling agent of 9% by weight of the pressed material and dopamine of 4% by weight of the silane coupling agent are added, and the pH of the material in the reactor is adjusted to 7.7. Under the condition of a stirring speed of 360 r / min, the stirring reaction is carried out for 35 minutes, and then the material is discharged, and then vacuum freeze-dried to obtain freeze-pressed chopped carbon fibers; and the carbon fibers are used as thermal conductive fillers;

[0054] The silane coupling agent is selected from silane coupling agent KH-550;

[0055] Weighing raw materials:

[0056] By weight, take 55 parts of vinyl silicone oil, 0.65 parts of platinum catalyst, 9 parts of hydrogenated silicone oil, 7 parts of thermal conductive filler, and 9 parts of thermoplastic elastomer;

[0057] Preparation of thermal conductive silicone:

[0058] Vinyl silicone oil, platinum catalyst, thermal conductive filler and thermoplastic elastomer are heated, stirred and mixed for 3 hours at a temperature of 90°C and a stirring speed of 450r / min, so that the thermoplastic elastomer is fully melted and the components are evenly mixed; hydrogen-containing silicone oil is then added, and the mixture is stirred and mixed for 50 minutes, and then injected into a mold, and after being heat-cured at a temperature of 90°C, cooled, and demolded to obtain thermal conductive silicone;

[0059] The thermoplastic elastomer is selected from styrene-butadiene-styrene triblock copolymers.

[0060] Example 3

[0061] Preparation of freeze-pressed chopped carbon fibers:

[0062] The carbon fiber and the polyvinyl alcohol solution with a mass fraction of 8% were mixed in a mass ratio of 1:12, stirred and mixed with a stirrer at a speed of 300 r / min for 40 minutes, and then frozen into a solid state at a temperature of -45°C, and then freeze-pressed for 30 seconds at a pressure of 15 MPa to obtain a pressed material;

[0063] The aspect ratio of the carbon fiber is 400, and the average length of the carbon fiber is 0.5 mm;

[0064] After the pressed material is completely thawed at room temperature, it is introduced into a reactor, and a silane coupling agent of 10% by weight of the pressed material is added, and dopamine of 5% by weight of the silane coupling agent is added, and the pH of the material in the reactor is adjusted to 7.8. Under the condition of a stirring speed of 380 r / min, the stirring reaction is carried out for 40 minutes, and then the material is discharged, and then vacuum freeze-dried to obtain freeze-pressed chopped carbon fibers; and the carbon fibers are used as thermal conductive fillers;

[0065] The silane coupling agent is selected from silane coupling agent KH-560;

[0066] Weighing raw materials:

[0067] By weight, take 60 parts of vinyl silicone oil, 0.7 parts of platinum catalyst, 10 parts of hydrogenated silicone oil, 8 parts of thermal conductive filler, and 10 parts of thermoplastic elastomer;

[0068] Preparation of thermal conductive silicone:

[0069] Vinyl silicone oil, platinum catalyst, thermal conductive filler and thermoplastic elastomer are heated, stirred and mixed for 2 hours at a temperature of 100°C and a stirring speed of 500r / min, so that the thermoplastic elastomer is fully melted and the components are evenly mixed; hydrogen-containing silicone oil is then added, and the mixture is stirred and mixed for 60 minutes, and then injected into a mold, and after heat preservation and curing at a temperature of 100°C, cooled, and demolded to obtain thermal conductive silicone;

[0070] The thermoplastic elastomer is selected from isoprene-substituted butadiene block styrene polymers.

[0071] Example 4

[0072] The difference between this embodiment and embodiment 1 is that dopamine is not added, and other conditions remain unchanged.

[0073] Example 5

[0074] The present embodiment differs from the embodiment 1 in that no silane coupling agent is added, and the other conditions remain unchanged.

[0075] Comparative Example 1

[0076] The difference between this comparative example and Example 1 is that no thermoplastic elastomer is added, and other conditions remain unchanged.

[0077] Comparative Example 2

[0078] Compared with Example 1, this comparative example has the following differences:

[0079] Carbon fibers with an aspect ratio of 200 and an average length of 0.3 mm were directly used as thermal conductive fillers without freeze pressing treatment, and other conditions remained unchanged.

[0080] Comparative Example 3

[0081] Compared with Example 1, this comparative example has the following differences:

[0082] The carbon fiber is added into a pulverizer and pulverized, and then the carbon fiber with an average length of 0.02 mm is sieved out, and then the carbon fiber is put into a reactor, and a polyvinyl alcohol solution with a mass fraction of 8% that is 10 times the mass of the carbon fiber is added, and the mixture is stirred and dispersed to obtain a carbon fiber dispersion, and then a silane coupling agent with a mass fraction of 8% of the carbon fiber dispersion is added, and dopamine with a mass fraction of 3% of the silane coupling agent is added, and the pH value of the material in the reactor is adjusted to 7.6. Under the condition of a stirring speed of 300 r / min, the reaction is stirred for 30 minutes, and then the material is discharged, and then vacuum freeze-dried to obtain a thermal conductive filler; the other conditions remain unchanged.

[0083] The performance tests were performed on the products obtained in the examples and comparative examples. The specific test methods and test results are as follows:

[0084] The mechanical properties and thermal conductivity of the products obtained in the above examples and comparative examples were tested according to the following standards:

[0085] According to GB / T 1040.1-2018, the elongation at break of the product is tested at a rate of 10 mm / min. For the same embodiment or comparative example, three samples are taken for testing and the average value is taken.

[0086] The thermal diffusion coefficient of the product is tested according to GB / T 22588-2008, the unit is mm 2 / s; Test product density according to GB / T1033.1-2008, unit is g / cm 3 ; The specific heat capacity was tested using a DSC instrument, the atmosphere was high-purity nitrogen, the air flow rate was 20 mL / min, the heating rate was 10 °C / min, and the unit was J / (g·K);

[0087] The thermal conductivity is calculated by referring to the following formula: Thermal conductivity 1 = density * thermal diffusion coefficient * specific heat capacity

[0088] The detailed test results are shown in Table 1;

[0089] The products obtained in the above embodiments and comparative examples were placed in an incubator at a temperature of 65°C and a relative humidity of 70% for 4 hours, taken out, and allowed to stand at room temperature for 4 hours. After this cycle was repeated 30 times, the mechanical properties and thermal conductivity were tested again according to the above standards to obtain the elongation at break 2 and the thermal conductivity 2. The detailed test results are shown in Table 1.

[0090] Table 1: Product performance test results

[0091]

[0092] It can be seen from the test results in Table 1 that the product obtained by the present invention has good mechanical properties and thermal conductivity, and can still maintain good performance after a long-term temperature shock aging test.

[0093] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing thermally conductive silica gel, characterized in that: The specific preparation steps include: Weighing raw materials: By weight, take 50-60 parts of vinyl silicone oil, 0.6-0.7 parts of platinum catalyst, 8-10 parts of hydrogenated silicone oil, 6-8 parts of thermal conductive filler, and 8-10 parts of thermoplastic elastomer; Wherein, the thermally conductive filler is freeze-pressed chopped carbon fiber; The preparation of the freeze-pressed chopped carbon fibers comprises: The carbon fiber and polyvinyl alcohol solution are stirred and mixed in a mass ratio of 1:10-12, and then frozen into a solid state at a temperature of -30-45°C, and then frozen and pressed for 20-30s at a pressure of 10-15MPa to obtain a pressed material; The pressed material is vacuum freeze-dried to obtain freeze-pressed chopped carbon fibers; Preparation of thermal conductive silicone: After heating and stirring the vinyl silicone oil, platinum catalyst, thermal conductive filler and thermoplastic elastomer to mix evenly, add hydrogen-containing silicone oil, continue to stir and mix evenly, inject into the mold, heat-insulate and cure, cool, and demold to obtain thermal conductive silicone.

2. The method for preparing a thermally conductive silica gel according to claim 1, characterized in that: The aspect ratio of the carbon fiber is 200-400, and the average length of the carbon fiber is 0.3-0.5 mm.

3. The method for preparing a thermally conductive silica gel according to claim 1, characterized in that: The thermoplastic elastomer is selected from any one of styrene-butadiene-styrene triblock copolymers or isoprene-substituted butadiene block styrene polymers.

4. The method for preparing a thermally conductive silica gel according to claim 1, characterized in that: The preparation of the thermally conductive silica gel also includes: Vinyl silicone oil, platinum catalyst, thermal conductive filler and thermoplastic elastomer are heated, stirred and mixed for 2-4 hours at a temperature of 80-100°C and a stirring speed of 400-500r / min, and then hydrogen-containing silicone oil is added. After continuing to stir and mix for 30-60 minutes, it is injected into a mold, and after heat preservation and curing at a temperature of 80-100°C, it is cooled and demolded to obtain thermal conductive silicone.

5. The method for preparing a thermally conductive silica gel according to claim 1, characterized in that: The preparation of the freeze-pressed chopped carbon fibers also includes: The carbon fiber and the polyvinyl alcohol solution with a mass fraction of 6-8% are stirred and mixed in a mass ratio of 1:10-12, and then frozen into a solid state at a temperature of -30-45°C, and then frozen and pressed for 20-30s at a pressure of 10-15MPa to obtain a pressed material; After the pressed material is completely thawed at room temperature, 8-10% of the mass of the pressed material is added with a silane coupling agent, the pH is adjusted to 7.6-7.8, and the reaction is stirred for 30-40 minutes at a stirring speed of 300-380 r / min, and then vacuum freeze-dried to obtain freeze-pressed chopped carbon fibers.

6. The method for preparing a thermally conductive silica gel according to claim 5, characterized in that: The silane coupling agent is selected from any one of silane coupling agent KH-540, silane coupling agent KH-550, silane coupling agent KH-560, silane coupling agent KH-570 and silane coupling agent KH-580.

7. The method for preparing thermally conductive silica gel according to claim 5, characterized in that: The preparation of the freeze-pressed chopped carbon fibers further comprises, when adding the silane coupling agent, adding dopamine in an amount of 3-5% by mass of the silane coupling agent.

8. A thermally conductive silica gel, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation process of low-viscosity low-modulus high-thermal-conductivity single-component gel

    CN115960463A

  • Thermally conductive silicone composition and method for producing the same

    CN118055971A

  • Heat conductive paste

    JP2008031295A